Is The Human Capital Investment of Provincial Governments Productive in Decentralization Era? - Bambang Suprayitno; Tejo Nurseto; Supriyanto Supriyanto (Faculty of Economics Universitas Negeri Yogyakarta in collaboration with the Institute for, 2017)
Abstract: Is The Human Capital Investment of Provincial Governments Productive in Decentralization Era? The effectiveness of government spending, especially investment in human capital, increases labor productivity also depends on how the local government determines the type of expenditure. The purpose of this study is to determine the effect of government spending in general and functionally to labor productivity. The approach used in this study is a quantitative approach, econometric method. This study uses secondary data from local government budgets across Indonesia summary provided by the Indonesian Ministry of Finance Directorate General of Regional Financial Balance. The data used is the provincial-level economic analysis units throughout Indonesia in 2012. This research shows that provincial government spending in human capital investment does not effectively increase labor productivity. Total provincial government spending does not affect the regional labor productivity. Government spending in the areas of public facilities and housing positively influence regional labor productivity. Keywords: local government, human capital investment, labor productivity, fiscal decentralization, public spendingAbstrak: Produktifkah Human Capital Investment oleh Pemerintah Daerah Provinsi dalam Era Desentralisasi? Efektivitas pengeluaran pemerintah khususnya human capital investment dalam meningkatkan produktivitas tenaga kerja juga tergantung dari pemilihan pemda dalam menentukan jenis pengeluaran tersebut. Tujuan dari penelitian ini untuk mengetahui pengaruh pengeluaran belanja pemerintah secara umum maupun secara fungsional terhadap produktivitas tenaga kerja melalui pendekatan kuantitatif dengan metode ekonometrika. Penelitian ini menggunakan data sekunder dari ringkasan APBD pemda seluruh Indonesia yang disediakan oleh Kemenkeu Dirjen Perimbangan Keuangan Daerah RI. Data yang digunakan adalah data tahun 2012 dengan unit analisis perekonomian level provinsi seluruh Indonesia. Pengeluaran pemerintah provinsi secara total tidak mempengaruhi produktivitas tenaga kerja regional. Pengeluaran pemerintah daerah provinsi dalam fungsi human capital investment tidak efektif meningkatkan produktivitas tenaga kerja meski demikian pengeluaran pemerintah dalam bidang fasilitas umum dan perumahan mempengaruhi secara positif produktivitas tenaga kerja regionalnya. Kata Kunci: pemerintah daerah, human capital investment, produktivitas tenaga kerja, desentralisasi fiskal, pengeluaran pemerintah